Flow characteristics and velocity fields of a front opening unified pod at open door condition. (October 2020) - Lin, Tee; Zargar, Omid Ali; Sabusap, Dexter Lyndon; Juiña, Oscar; Lee, Tzu-Chieh; Hu, Shih-Cheng; Leggett, Graham
Abstract: Particle contamination decreases product quality in semiconductor industries. Nowadays, the size of the chips and features has significantly reduced; thus increasing the importance of moisture removal from front opening unified pods during manufacturing and transportation of semiconductor wafers. An innovative laminar air curtain and a diffuser purge device were designed at Taipei Tech. These devices are currently used in many semiconductor industries. Smoke flow visualization was used in the present study to evaluate and justify the performance of three different moisture removal methods: air curtain, conventional purge, and diffuser purge. A mini-environment and front opening unified pod model were constructed with the same size and shape as the real applications at manufacturing facilities. An innovative laser sweep technique was designed at Taipei Tech, which can provide a plane laser light sheet during the experiments. The smoke flow patterns were recorded by a digital camera. The relative humidity was monitored using relative humidity sensors that were installed on dummy wafers inside the front opening unified pod. Study of the flow patterns, velocity fields, and relative humidity data show that the combination of air curtain and diffuser purge techniques presented the highest performance, and is therefore recommended to the industry.